The role of peptide and DNA vaccines in myeloid leukemia immunotherapy - Lin Chen; Li Yangqiu (Cancer Cell International, 2013)
Abstract While chemotherapy and targeted therapy are successful in inducing the remission of myeloid leukemia as acute myeloid leukemia (AML) and chronic myeloid leukemia (CML), the disease remains largely incurable. This observation is likely due to the drug resistance of leukemic cells, which are responsible for disease relapse. Myeloid leukemia vaccines may most likely be beneficial for eradicating minimal residual disease after treatment with chemotherapy or targeted therapy. Several targeted immunotherapies using leukemia vaccines have been heavily investigated in clinical and preclinical trials. This review will focus on peptides and DNA vaccines in the context of myeloid leukemias, and optimal strategies for enhancing the efficacy of vaccines based on myeloid leukemia immunization are also summarized.